2018
DOI: 10.1089/pho.2017.4364
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photobiomodulation and Anti-Inflammatory Drugs on Tissue Repair on Collagenase-Induced Achilles Tendon Inflammation in Rats

Abstract: LLLT showed a significant superiority over commonly used anti-inflammatory pharmaceutical agents in acute collagenase-induced tendinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
2
15
2
7
Order By: Relevance
“…A tendency towards higher fluorescence intensity of the ASCs-GFP was observed in the SCL group compared to the SC. No differences were observed in the expression of Tgfb1 among groups, but the higher concentration of IL-10 in the SC group corroborates the Our results do not demonstrate differences in the amount of TNF-α in the different groups, although the literature describes the anti-inflammatory role of LLL 38 and ASCs. 9 A previous study of our group has shown the presence of transplanted ASCs on 3rd and 14th days after tendon transection, probably in response to the intense initial inflammatory process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A tendency towards higher fluorescence intensity of the ASCs-GFP was observed in the SCL group compared to the SC. No differences were observed in the expression of Tgfb1 among groups, but the higher concentration of IL-10 in the SC group corroborates the Our results do not demonstrate differences in the amount of TNF-α in the different groups, although the literature describes the anti-inflammatory role of LLL 38 and ASCs. 9 A previous study of our group has shown the presence of transplanted ASCs on 3rd and 14th days after tendon transection, probably in response to the intense initial inflammatory process.…”
Section: Discussionsupporting
confidence: 89%
“…36 Our data showed no difference in the proliferator marker, as well showed increased apoptosis after association of treatments in comparison with LLL. It is important to emphasize that the increased Our results do not demonstrate differences in the amount of TNF-α in the different groups, although the literature describes the anti-inflammatory role of LLL 38 and ASCs. 39 Regarding the F I G U R E 5 A, ELISA for the analysis of cytokines IL-10 and TNF-α (pg/mL).…”
Section: Discussioncontrasting
confidence: 53%
“…Regardless of aforementioned limitations, the included studies investigated several inflammatory mediators, such as pro-inflammatory mediators (interleukin-1 beta (IL-1b), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-a), cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2) and transforming growth factor beta (TGF-b)) (10)(11)19,21,(23)(24)27,33,35,39,(47)(48)(50)(51)(52)(53), as well as anti-inflammatory mediator [interleukin-10 (IL-10)] (21,30,48), involved in tendon repair or tendinitis condition. Other inflammatory mediator factors were also studied such as vascular endothelium growth factor (VEGF), metalloproteinase-1 matrix (MMP1), metalloproteinase-2 matrix (MMP-2), metalloproteinase-3 matrix (MMP-3), metalloproteinase-9 matrix (MMP-9), metalloproteinase-13 matrix (MMP13) and induced nitric oxide synthase (i-NOS) (10)(11)(28)(29)(34)(35)37,39,54) that contribute to the understanding of how PBMT can benefited tendon repair or tendinitis condition. In this context, depending on wavelength, dose (Joule), treatment frequency and tendon repair phase, PBMT, either by LLLT or by LED, can modulate levels of gene expression (mRNA), enzymatic activity of metalloproteinases (MMPs) (11,(27)(28)35,39) and collagen synthesis (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…Naterstad et al (34) established in their study that neutrophils are the first cells to reach the site of injury (tendinitis) and other inflammatory cells, such as macrophages, migrate to the site of injury by chemotaxis, with increased levels of cytokines, reactive oxygen species and proteases. In this context, Enwemeka and Reddy (54) showed that 4 days after injury, there will be an increase in mRNA expression for all NOS isoforms, accentuating the inflammatory process, because the i-NOS peak occurs at the beginning of the inflammatory process, and subsequently, the levels of NO production are maintained by the other isoforms of NOS (39).…”
Section: Referencementioning
confidence: 99%
“…Os resultados encontrados por Naterstad et al (2017) e Gomes et al (2017) podem ser justificados por Pessoa et al (2017) Isso ocorre porque, mesmo havendo recomendação da Associação Mundial para fotobiomodulação sobre a dose adequada de energia para cada comprimento de onda, ainda existem dúvidas sobre a dose e o comprimento de onda ideal, como confirmado pela análise criteriosa dos estudos. Sugere-se, então, a utilização dos seguintes parâmetros dosimétricos: comprimento de onda (730 -830 nm), potência da luz (60 mW a 100 mW), energia (2 a 8 J), densidade de potência (até 37 J/cm 2 por ponto de irradiação) e densidade de potência (1.…”
Section: Discussionunclassified